Pengembangan Aplikasi Pengolah Kata Menggunakan C++ Builder 5.0 - Lukman Effendi (Universitas Darussalam Gontor, 2016)
A word processor is a tool used for writing text in which a word processing application has a function can perform text editing and printing. In making the word processing application is used programming languages C ++ Builder 5.0. The logic flow of this first-word processing application user will be presentedwith a form where there is a place to write the text. Within these forms are also several main menus in which there is a menu that is used to create new documents, the menu is used to edit the text, the menuis used for printing, as well as a menu that is used to store documents that support the format: txt, rtf, doc.